2022
DOI: 10.1186/s42483-022-00134-0
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and management of peach diseases

Abstract: Peach is a popular and important tree fruit widely produced in the world, and the production of high-quality peach fruit does require management of pests and diseases. In this review, major peach diseases from China, Spain, and USA are described in detail for the benefit of producers, consultants, researchers, and other interested parties. Minor diseases of concern in these countries are also described. Current progress on pathogen resistance to major chemical classes of fungicides as well as current resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Variations in temperature from extreme low to extreme high are occurring, affecting the development of any crop. Integration of many aspects, such as proper fertilization with mineral nutrients like iron, nitrogen, potassium, magnesium, and phosphorus, has a relevant impact on fruit load and quality [25,78], soil quality, water availability, pest management, viruses, and bacteria are determined with economic importance on the reduction of physical peach characteristics and production, crop genetics using potential genes in peaches to enhance the fruit characteristics and production [79], among others, play vital roles in fruit quality and yield [25,[78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in temperature from extreme low to extreme high are occurring, affecting the development of any crop. Integration of many aspects, such as proper fertilization with mineral nutrients like iron, nitrogen, potassium, magnesium, and phosphorus, has a relevant impact on fruit load and quality [25,78], soil quality, water availability, pest management, viruses, and bacteria are determined with economic importance on the reduction of physical peach characteristics and production, crop genetics using potential genes in peaches to enhance the fruit characteristics and production [79], among others, play vital roles in fruit quality and yield [25,[78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these metabolites or their constituents may be employed as indicators to identify specific fungal species PLSR was performed on EN sensory array to develop a model showing the correlation between EN and colony-forming units (R 2 = 0.883-0.908, RMSEP = 0.235-0.435 log (CFU g −1 ), and RPD = 2.80-4.16). The authors also reported that the results showed successful discrimination among healthy and disease-infected samples after 48 h. This research can also further investigate detecting other common postharvest diseases of peaches such as bacterial spot, peach constriction canker, powdery mildew, or peach shot hole to name a few (Luo et al, 2022) Shen et al ( 2018) have derived the feasibility of EN and other tools of analysis in detecting the contamination level of five Aspergillus strains on peanuts. Peanut samples were sterilized and artificially infected with fungi and stored for 9 days until they turned moldy.…”
Section: En For Early Detection Of Postharvest Diseasesmentioning
confidence: 85%
“…[ 13 ]. Worldwide, peach branch diseases including gummosis trunk, trunk canker, twig canker, twig spots, and shoot blight have been commonly observed, particularly in regions where stress factors are prevalent [ 14 , 15 ]. To date, there has been no comprehensive study on microfungi associated with peach branch diseases in China.…”
Section: Introductionmentioning
confidence: 99%